The Calliphoridae of Namibia (Diptera: Oestroidea) - Kurahashi, Hiromu; Kirk-Spriggs, Ashley H. (Zootaxa, 2006)
The Namibian Calliphoridae fauna is reviewed. Seventy-five nominate species are recorded from the country, based on 7100 specimens housed in the Namibian National Insect Collection. Identification keys to all taxa are provided, together with notes on biology and new biological observations. An annotated checklist of Namibian species is presented, detailing previously published and other known Namibian records, and distributions elsewhere in Africa. Provisional distribution maps are plotted and discussed. Seasonal data, based on specimen label information, are presented in tabular form. The known immature stages of species are reviewed, together with notes on the forensic significance of relevant species. Two new species of the genus Hemigymnochaeta Corti and one new species of Isomyia Walker are described and illustrated, namely: Hemigymnochaeta maraisi Kurahashi and Kirk-Spriggs, sp. nov., Hemigymnochaeta trichaeta Kurahashi and Kirk-Spriggs, sp. nov., and Isomyia hauwangai Kurahashi and Kirk-Spriggs, sp. nov. Rhyncomya zumpti Peris, 1952 stat. rev., formerly synonymised with R. tristis Séguy, 1933, is here reinstated as a valid species. Thirty-four species are new to the Namibian list, namely: Bengalia spinifemorata Villeneuve, Chrysomya ?laxifrons Villeneuve, C. putoria (Wiedemann), Cosmina fuscipennis Robineau-Desvoidy, C. undulata Malloch, Fainia albitarsis (Macquart), Hemigymnochaeta bequaerti Curran, H. laticeps Zumpt, Isomyia darwini (Curran), I. deserti (Karsch), I. natalensis (Villeneuve), I. tristis (Bigot), Neocordylobia roubaudi Villeneuve, Perisiella anchora (Wiedemann), Phumosia nanoides Zumpt, Pseudorhyncomyia braunsi (Villeneuve), Rhyncomya bicolor (Macquart), R. cassotis (Walker), R. discrepans Villeneuve, R. hessei Zumpt, R. messoria Villeneuve, R. minutalis Villeneuve, R. io Peris, R. peraequa Villeneuve, R. soyauxi Karsch, R. trispina Villeneuve, R. tristis Séguy, R. zumpti Peris, Stegosoma vinculatum Loew, Stomorhina chapini Curran, S. rugosa (Bigot), Tricyclea claripennis Séguy, T. flavida (Malloch), and T. martini (Zumpt). Records of species from other southern African countries, based on 190 specimens housed in the Namibian National Insect Collection, are provided as an Appendix. Cosmina gracilis Curran and Rhyncomya dasyops Bezzi are new to Angola; Auchmeromyia bequaerti Roubaud and Bengalia cuthbertsoni Zumpt are new to Botswana; B. floccosa (van der Wulp), B. peuhi (Brauer and Bergenstamm) and Hemigymnochaeta unicolor (Bigot) are new to Zambia; and Cosmina gracilis Curran and Tricyclea martini (Zumpt) are new to Zimbabwe.